″Essential characteristics of the quality of higher education as the basis for the management of professional education of a modern specialist.″ - Pohorielova T. Yи. (Problems of Engineer-Pedagogical Education, 2018)
The topicality of the article is explained by the fact that the study of indicators of the quality of education is one of the main conditions for the management of the national system of the quality of higher education. The research is based on a number of scientific papers by foreign and domestic authors, who reviewed the quality of education in various aspects, and a number of normative documents. The article analyzes the origin of the notion of quality, its formation and modern definitions, justifies the importance of quality control of the educational process in higher educational institutions and highlights the role of the interaction between teachers and students as central subjects of the educational process. The article outlines general criteria and indicators according to which the strategy of quality assurance in higher educational institutions should be implemented and defines indicators of the effective interaction between teachers and students. The key issues for further research on the quality of higher education may include elaboration of principles and methods for measuring educational achievements and development of a system of fair criteria for evaluating the efficiency of teachers‟ activity and that of the other participants of the educational process.